Avaliação da densidade mineral óssea com bioimpedância: estudo de viabilidade - Albuquerque, Diogo de Azevedo Resende de (2025)
Osteoporosis is characterized by the alteration of bone microarchitecture and, consequently, a decrease in bone mineral density, a factor that results in a significant increase in fracture risk. Despite the clinical and epidemiological relevance of this disease, there is no cost-effective method for screening. Dual-energy X-ray absorptiometry (DXA) is the diagnostic method of choice, although its application is restricted to specific groups. While it is the reference standard, DXA has a low predictive capacity for fractures in asymptomatic patients, as 80% of bone fragility fractures occur in individuals with a T-score above -2.5, the threshold for an osteoporosis diagnosis. In this context, it is necessary to evaluate more accessible and effective complementary tests. Bioelectrical impedance analysis (BIA) has emerged as a useful tool for screening and diagnosing bone mineral density (DMO), with potential advantages over DXA. Based on this possibility, a systematic review was conducted to investigate the association between bioelectrical parameters—such as resistance (R), reactance (Xc), phase angle (PhA) and DMOvalues. Seventeenth studies were analyzed in which the direct measurement of DMO by BIA was evaluated using various parameters, including impedance (Z), resistance (R), reactance (Xc) and phase angle (PhA). The results of the review show statistically significant correlations between DMO values measured by DXA and BIA. Despite these findings, BIA can present significant limitations in quantitative accuracy compared to DXA for the direct estimation of bone mass due to systematic and proportional biases, as well as wide individual variability. Nevertheless, multifactorial predictive equations and the phase angle (at 50 kHz) demonstrate potential for high precision, suggesting greater applicability as a complementary screening tool, especially in at-risk populations and in contexts with limited resources.